Exploring The Role of Digital Literacy in Teaching And Learning English as A Foreign Language In 9th Grade SMP NW Kalijaga - Maezura, Siti; Zamzam, Ahmad; Saputra, Agus (Journal of Authentic Research, 2026)
In today's digital era, digital literacy is a crucial competency that students must master to support successful learning, including in learning English as a foreign language. However, in many rural schools in Indonesia, students' digital literacy skills still face various challenges such as limited internet access, lack of technical guidance, and poor ability to evaluate online information. This study aims to explore the role of digital literacy in English learning for 9th-grade students at NW Kalijaga Junior High School and identify the challenges and strategies used by students. The study used a qualitative, descriptive approach. Data were collected through structured observations, semi-structured interviews, documentation, and questionnaires with a Likert scale of 1–4. Data were analyzed using thematic analysis. The results show that digital literacy helps students access learning materials, understand lessons, complete assignments, and communicate through digital media. Platforms such as WhatsApp and Canva also enhance student interaction and creativity. Quantitatively, 83.3% of students agreed that digital literacy helps evaluate information, and 88.9% agreed that digital literacy supports creativity. However, students still face challenges such as limited internet access (69.8% admitted to experiencing this), difficulty understanding digital instructions, and limited ability to evaluate online information. The strategies used by students included seeking information from various sources, comparing content, and asking teachers or peers. This study concluded that digital literacy plays a crucial role in supporting English learning, but requires improved infrastructure and teacher support. Practical implications of this research include the need for integrated digital literacy training and the provision of stable internet access in rural schools.